Shelf life of frozen desalted cod (Gadus morhua) ... - Dargentolle, Cecile; Sveinsdóttir, Hildur Inga; Baldursson, Jónas; Arason, Sigurjón; Sveinsdóttir, Kolbrún (Zenodo, 2024)
A part of the project „Saltfiskur til framtíðar“ was to study the quality and shelf life of desalted cod in frozen storage. The focus of the experiment described in this report was on desalting of loins and tail parts of fully salt cured cod fillets, followed by three different types of treatment before frozen storage. The first group was frozen and then glazed, packed in plastic and carboard boxes, the second group was frozen and then glazed and vacuum packed, and the third group was treated with citric acid (0.2 %), then frozen, glazed and vacuum packed. Before the treatments, samples were split into either loin or tail samples within each group. The quality and shelf life of the three groups, both loins and tails were evaluated at the beginning of storage and after 6, 9, 12 and 27 months of frozen storage at -25°C, by sensory evaluation, microbiological and chemical analysis. The three treatments did not significantly affect the shelf life of the frozen desalted cod samples, and even after 27 months of ...